Tandem-Mass-Tag Based Proteomic Analysis Facilitates Analyzing Critical Factors of Porous Silicon Nanoparticles in Determining Their Biological Responses under Diseased Condition - Yunzhan Li; Zehua Liu; Li Li; Wenhua Lian; Yaohui He; Elbadry Khalil; Ermei Mäkilä; Wenzhong Zhang; Giulia Torrieri; Xueyan Liu; Jingyi Su; Yuanming Xiu; et al. (WILEY, 2022)
The analysis of nanoparticles' biocompatibility and immunogenicity is mostly performed under a healthy condition. However, more clinically relevant evaluation conducted under pathological condition is less known. Here, the immunogenicity and bio-nano interactions of porous silicon nanoparticles (PSi NPs) are evaluated in an acute liver inflammation mice model. Interestingly, a new mechanism in which PSi NPs can remit the hepatocellular damage and inflammation activation in a surface dependent manner through protein corona formation, which perturbs the inflammation by capturing the pro-inflammatory signaling proteins that are inordinately excreted or exposed under pathological condition, is found. This signal sequestration further attenuates the nuclear factor kappa B pathway activation and cytokines production from macrophages. Hence, the study proposes a potential mechanism for elucidating the altered immunogenicity of nanomaterials under pathological conditions, which might further offer insights to establish harmonized standards for assessing the biosafety of biomaterials in a disease-specific or personalized manner.